Knockdown of SPON2 inhibits the growth of triple-negative breast cancer - Hu, Xueyi; Su, Caiwu; Wei, Jian (Frontiers in Oncology, 2023)
Objective Spondin-2 (SPON2) is highly expressed in a variety of tumors and has been associated with poor prognosis, but the relationship to triple-negative breast cancer (TNBC) is unclear. The aim of this study is to investigate the expression of SPON2 in TNBC and its function. Methods Immunohistochemistry was used to detect the expression of the SPON2 protein in TNBC and in normal tissue adjacent to cancer and breast fibroadenoma. The GEO database GSE76275 dataset was used to study the expression of SPON2 mRNA in TNBC and non-TNBC. ​The expression of SPON2 mRNA was detected by qPCR in TNBC cells MDA-MB-231, non-TNBC breast cancer cells MCF-7, and normal breast cells MCF-10A. ​Kaplan Meier-Plotter database was used to analyze the relationship between SPON2 expression and TNBC prognosis. ​ShRNA lentivirus was used to knock down high expression of SPON2 in TNBC cells. The effects of knockdown of SPON2 expression on the proliferation, migration, invasion, apoptosis, and subcutaneous tumorigenic ability of TNBC cells in nude mice were analyzed using CCK8, clone formation assay, scratch assay, transwell migration assay, transwell invasion assay, Hoechst apoptosis assay, and tumorigenic ability in nude mice. Transcriptome sequencing of TNBC cells with knockdown SPON2 expression. ​In combination with the GEO database, GO and KEGG analyses were performed, and psychophysiological interaction Protein-Protein Interaction Networks (PPI) analysis was performed for transcriptome sequencing of the differentially expressed genes. ​The changes in the expression of PI3K-ATK pathway proteins after SPON2 knockdown were detected by Western blot. Results Our study shows that upregulation of SPON2 in TNBC is associated with poorer patient outcomes. Knockdown of SPON2 inhibited TNBC cell proliferation, clone formation, migration, invasion, and tumorigenic ability and promoted apoptosis. Knockdown of SPON2 up-regulated TNBC cell adhesion and down-regulated PI3K-ATK pathway, and PPI results showed that CCL2 was the key protein. Conclusions SPON2 may be a valuable biomarker for the diagnosis and prognosis of TNBC and is a potential therapeutic target for TNBC.